Effect of Korea red ginseng on nonalcoholic fatty liver disease: an association of gut microbiota with liver function - Hong, Ji Taek (J Ginseng Res, 2021)
BACKGROUND: Korea Red Ginseng (KRG) has been used as remedies with hepato-protective effects in liver-related condition. Microbiota related gut-liver axis plays key roles in the pathogenesis of chronic liver disease. We evaluated the effect of KRG on gut-liver axis in patients with nonalcoholic statohepatitis by the modulation of gut-microbiota. METHODS: A total of 94 patients (KRG: 45 and placebo: 49) were prospectively randomized to receive KRG (2,000 mg/day, ginsenoside Rg1+Rb1+Rg3 4.5mg/g) or placebo during 30 days. Liver function test, cytokeraton 18, and fatigue score were measured. Gut microbiota was analyzed by MiSeq systems based on 16S rRNA genes. RESULTS: In KRG group, the mean levels (before vs. after) of aspartate aminotransferase (53 ± 19 vs. 45 ± 23 IU/L), alanine aminotransferase (75 ± 40 vs. 64 ± 39 IU/L) and fatigue score (33 ± 13 vs. 26 ± 13) were improved (p < 0.05). In placebo group, only fatigue score (34 ± 13 vs. 31 ± 15) was ameliorated (p < 0.05). The changes of phyla were not statistically significant on both groups. In KRG group, increased abundance of Lactobacillus was related with improved alanine aminotransferase level and increased abundance of Clostridium and Intestinibacter was associated with no improvement after KRG supplementation. In placebo group, increased abundance of Lachnospiraceae could be related with aggravation of liver enzyme (p < 0.05). CONCLUSION: KRG effectively improved liver enzymes and fatigue score by modulating gut-microbiota in patients with fatty liver disease. Further studies are needed to understand the mechanism of improvement of nonalcoholic steatohepatitis. CLNICALTRIALS.GOV: NCT03945123 (www.ClinicalTrials.gov).